Cross-sectional studies of tuberculosis prevalence in Cambodia between 2002 and 2011 - Tan Eang Mao; Kosuke Okada; Norio Yamada; Satha Peou; Masaki Ota; Saly Saint; Pichenda Kouet; Manith Chea; Sokonth Keo; Sok Heng Pheng; Sivanna Tieng; Kim Eam Khun; et al. (Bulletin of the World Health Organization)
Objective To measure trends in the pulmonary tuberculosis burden between 2002 and 2011 and to assess the impact of the DOTS (directly observed treatment, short-course) strategy in Cambodia. Methods Cambodia’s first population-based nationwide tuberculosis survey, based on multistage cluster sampling, was conducted in 2002. The second tuberculosis survey, encompassing 62 clusters, followed in 2011. Participants aged 15 years or older were screened for active pulmonary tuberculosis with chest radiography and/or for tuberculosis symptoms. For diagnostic confirmation, sputum smear and culture were conducted on those whose screening results were positive. Findings Of the 40 423 eligible subjects, 37 417 (92.6%) participated in the survey; 103 smear-positive cases and 211 smear-negative, culture-positive cases were identified. The weighted prevalences of smear-positive tuberculosis and bacteriologically-positive tuberculosis were 271 (95% confidence interval, CI: 212–348) and 831 (95% CI: 707–977) per 100 000 population, respectively. Tuberculosis prevalence was higher in men than women and increased with age. A 38% decline in smear-positive tuberculosis (P = 0.0085) was observed with respect to the 2002 survey, after participants were matched by demographic and geographical characteristics. The prevalence of symptomatic, smear-positive tuberculosis decreased by 56% (P = 0.001), whereas the prevalence of asymptomatic, smear-positive tuberculosis decreased by only 7% (P = 0.7249). Conclusion The tuberculosis burden in Cambodia has declined significantly, most probably because of the decentralization of DOTS to health centres. To further reduce the tuberculosis burden in Cambodia, tuberculosis control should be strengthened and should focus on identifying cases without symptoms and in the middle-aged and elderly population.